2012
DOI: 10.1039/c2ce25505g
|View full text |Cite
|
Sign up to set email alerts
|

Exchange bias and magnetodielectric coupling effects in ZnFe2O4–BaTiO3 composite thin films

Abstract: Multiferroic composite thin films prepared from ferrimagnetic zinc ferrite (ZFO) and ferroelectric barium titanate (BTO) show sizable magnetic exchange bias. After field cooling in +3 T, an exchangebias field of about 237 mT for a 65% ZFO/35% BTO and of about 234 mT for a 35% ZFO/65% BTO composite is observed at 10 K. Exchange biasing is accompanied by a significant vertical loop shift of about 10% of the total saturation magnetization after field cooling in 3 T. The composite films show simultaneous ferromagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…This effect has already been observed in nanocrystalline BTO samples (Ding and Zhou 2011, Cao et al 2009, Sundaresan and Rao 2009 and is found to be induced by oxygen and titanium vacancies. In our previous work (Lorenz et al 2012), we found for the single-phase BTO film a similar magnetic signal, and this defect-induced magnetism is now established for other nominal nonmagnetic oxide thin films such as undoped ZnO (Khalid et al 2009) and ZrO 2 (Zippel et al 2013). Therefore, both BFO and BTO layered phases possess weak net magnetic moments.…”
Section: Multiferroic Propertiessupporting
confidence: 69%
See 1 more Smart Citation
“…This effect has already been observed in nanocrystalline BTO samples (Ding and Zhou 2011, Cao et al 2009, Sundaresan and Rao 2009 and is found to be induced by oxygen and titanium vacancies. In our previous work (Lorenz et al 2012), we found for the single-phase BTO film a similar magnetic signal, and this defect-induced magnetism is now established for other nominal nonmagnetic oxide thin films such as undoped ZnO (Khalid et al 2009) and ZrO 2 (Zippel et al 2013). Therefore, both BFO and BTO layered phases possess weak net magnetic moments.…”
Section: Multiferroic Propertiessupporting
confidence: 69%
“…To overcome the limitations of single-phase multiferroics, composite and multilayer multiferroics consisting of coupled magnetic and ferroelectric phases are promising to show higher magnetization values up to the order of tens of emu cm −3 (in SI units, 1 emu cm −3 = 10 3 A m −1 , corresponding to µ 0 M = 4π × 10 −4 T), and polarization up to tens of µC cm −2 (10 −2 C m −2 ), respectively (Lawes and Srinivasan 2011). For example, multiferroic ZnFe 2 O 4 /BaTiO 3 (ZFO/BTO) composite thin films show a magnetization of 8 and 30 emu cm −3 for the ZFO/BTO multilayer; and ferroelectric polarization around 8 µC cm −2 (Lorenz et al 2012). However, the magnetodielectric coupling in the ZFO/BTO composite films was found to be weak, of the order of 0.01% and 0.8% for the real and imaginary parts of the permittivity, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The lattice constants for ZFO and ZCO films are closer to the bulk values for samples grown at high temperature, as expected for a more ideal cubic structure . The shift of the lattice constant is due to fewer defects, such as cation disorder and oxygen vacancies, a lattice relaxation with increasing growth temperature is therefore observable (). The lattice constants of thin films, extrapolated from cos2false(Θfalse) and the literature bulk values are listed in Table 1.…”
Section: Methodssupporting
confidence: 62%
“…[3,24,26,28,29] The shift of the lattice constant is due to fewer defects, such as cation disorder and oxygen vacancies, a lattice relaxation with increasing growth temperature is therefore observable. [30] The lattice constants of thin films, extrapolated from cos 2 (Θ) and the literature bulk values are listed in Table 1.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…However, the crossover from negative to positive values of µ 0 H E shown in Figure d indicates the coexistence of different coupling mechanisms, given the fact that no external stimuli like temperature, electric or magnetic fields were used to influence this crossover phenomenology . Appropriately, an exchange bias mechanism with positive values of µ 0 H E associated to the interface between nanoparticles of the two different oxides in the composites (as sketched in Figure b) would increase its value as increasing the area of this interface, that is, as increasing the weight percentage of the cobalt ferrite (or decreasing the percentage of the chromium oxide) in the final composites. Indeed, for the two composite samples the three types of interfaces are present, being the most abundant interface the one between two Cr 2 O 3 nanoparticles in the S 25 composite sample, and the one between one nanoparticle of CoFe 2 O 4 and one nanoparticle of Cr 2 O 3 in the S 60 composite sample.…”
Section: Resultsmentioning
confidence: 97%